Is someone listening? The first IJTC National Survey of CTVS trainees - Shetty, Varun (Indian J Thorac Cardiovasc Surg, 2018)
Cardiothoracic surgery will soon have a shortage of qualified surgeons in India, because the profession is losing appeal among surgical residents. Do we really understand why the profession is not their first choice, or what the current cardiothoracic residents think about their training? This article is the first nationwide survey meant only for cardiothoracic residents in training, conducted through online survey tool to report on the issues concerning our residents.